2015
DOI: 10.3109/14397595.2015.1101200
|View full text |Cite
|
Sign up to set email alerts
|

RENACER study: Assessment of 12-month efficacy and safety of 168 certolizumab PEGol rheumatoid arthritis-treated patients from a Spanish multicenter national database

Abstract: CZP showed benefit in severe RA patients, with significant reduction of all effectiveness parameters, despite the high prevalence of previous BT exposure in our series. We found CRP, ESR, prior DMARD/BT number, TJC, SJC, DAS28, and SDAI as baseline predictors of response. CZP was mostly well tolerated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 31 publications
2
8
0
1
Order By: Relevance
“…The same study also demonstrated that longer disease duration and prior use of biologic DMARDs (TNFi), but not csDMARDs, was associated with significantly reduced likelihood of achieving sustained remission 18. Association between higher number of prior DMARDs and reduced likelihood of achieving treatment response has been demonstrated in a few other RA studies,14 19 20 including two certolizumab pegol studies 13 21. In our study, a greater number of prior DMARDs and longer disease duration were associated with significantly decreased odds of achieving improvement as measured by ACR response.…”
Section: Discussionsupporting
confidence: 74%
“…The same study also demonstrated that longer disease duration and prior use of biologic DMARDs (TNFi), but not csDMARDs, was associated with significantly reduced likelihood of achieving sustained remission 18. Association between higher number of prior DMARDs and reduced likelihood of achieving treatment response has been demonstrated in a few other RA studies,14 19 20 including two certolizumab pegol studies 13 21. In our study, a greater number of prior DMARDs and longer disease duration were associated with significantly decreased odds of achieving improvement as measured by ACR response.…”
Section: Discussionsupporting
confidence: 74%
“…Other real-world studies of certolizumab in RA patients have also found significant improvements. Two of them were registry-based studies in Sweden [ 26 ] and Italy [ 27 ] and the third was a Spanish observational multicenter study [ 28 ]. Study designs were different and EULAR response was evaluated at 6 months [ 26 , 27 ] and/or 1 year [ 27 , 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…Two of them were registry-based studies in Sweden [ 26 ] and Italy [ 27 ] and the third was a Spanish observational multicenter study [ 28 ]. Study designs were different and EULAR response was evaluated at 6 months [ 26 , 27 ] and/or 1 year [ 27 , 28 ]. Although certolizumab was effective and safe in all these studies, percentages of good response were different: 38 [ 26 ] and 65% [ 27 ] of patients at 6 months and 66 [ 27 ] and 46.4% [ 28 ] of patients at 12 months.…”
Section: Discussionmentioning
confidence: 99%
“…Some ‘real world’ studies have reported better outcomes than these meta‐analyses, with remission rates or remission/low disease activity (as defined by DAS28 score) as high as 44–63% 18,19 . In the British Society for Rheumatology (BSR) Biologics Registry for Rheumatoid Arthritis, remission (DAS28 <2.6) was achieved in about 15% and low disease activity (DAS28 2.6 to 3.2) in about 26% of patients treated with anti‐TNF therapy between 2001 and 2013 20 .…”
Section: Range Of Biological Therapies For Rheumatoid Arthritismentioning
confidence: 97%